User risky behavior and security awareness through lifespan - Velki, Tena (Array, 2019)
In the last decade, the internet has become a crucial part of human life. Everyday usage of the internet has enabled rapid development of social engineering. The weakest link in this chain are naive users with their risky online behavior who are unaware of internet security risks. As knowledge, awareness and behavior depend on human characteristics, such as maturity, age and education, the main goal of this study was to investigate trendlines of user risky behavior and security awareness through the lifespan. Results have shown the growth of online risky behavior through the lifespan and the growth of knowledge and security awareness in middle adulthood. In general, we can conclude that people who are more knowledgeable about and more aware of potential security risks are at the same time more prone to risky behavior when using information systems.